The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1516-3180.2016.0311271216
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms linking probiotics to diabetes: a narrative review of the literature

Abstract: CONTEXT AND OBJECTIVE: Some studies have suggested a wide range of possible mechanisms through which probiotics may play a role in diabetes prevention and treatment. However, the underlying mechanisms are not fully understood. We conducted this study to review the potential mechanisms suggested for the effect of probiotics in diabetes. DESIGN AND SETTING: Narrative review conducted at the Food Security Research Center of Isfahan. METHODS: A search in the electronic databases MEDLINE (PubMed), Cochrane Library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…This result is the first evidence reported in the literature, and we speculate that it could be attributed to the capacity of probiotics to decrease the intestinal permeability with a consequent reduction of lipopolysaccharide and inflammatory cytokine levels [58]. …”
Section: Discussionmentioning
confidence: 52%
“…This result is the first evidence reported in the literature, and we speculate that it could be attributed to the capacity of probiotics to decrease the intestinal permeability with a consequent reduction of lipopolysaccharide and inflammatory cytokine levels [58]. …”
Section: Discussionmentioning
confidence: 52%
“…A recent systematic review with DM2 patients showed that the use of probiotics reduced fasting blood glucose (in 19 studies), glycated haemoglobin (in 13 studies), insulin (in 13 studies) and HOMA-IR (in 10 studies) 13 . The potential mechanisms of probiotics actions on glycemic control are: 1) direct intraluminal effects on the microbiota, with increase in the production of short-chain fatty acids (SCFAs), intestinal permeability reduction and lipopolysaccharides, and increases the production of glucagon-like peptide 1 (GLP-1); 2) anti-inflammatory and immunomodulatory effects, with reduction of pro-inflammatory cytokines; 3) reduction of oxidative stress, with protective effect of beta cells; 4) effects of gene expression involved in glucose homeostasis and insulin resistance, as sensitization increases via GLUT-4 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Pepck and G6pc are key enzymes in a gluconeogenesis process. Pepck is an enzyme that catalyzes the synthesis of glucose-6-phosphate from noncarbohydrate precursors, while G6pc catalyzes the dephosphorylation of glucose-6phosphate to glucose, and this reaction is the last reaction step in gluconeogenesis [17]. Consumption of probiotics has been reported to ameliorate hyperglycemia [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%